Crise da legalidade estatal e política nacional de nanotecnologia: uma leitura sob a perspectiva da autêntica tradição constitucional - Valerio, Xana Campos (Universidade do Vale do Rio dos Sinos, 2014)
The issue of regulation or not the nanotechnology, with all the revolutionary possibilities its presents, permeates these two ways of understanding the tradition and interpret the life-world: institutionalism and utilitarianism. As antagonistic pre-understanding points of view, points to building a future from different perspectives: one that advocates maintaining a constitutional principle, that a democratic state should guide the action of the subject as part of the movement that happen to and happens the world, where the Constitution Leader and Democratic State constitute related necessary. Another one, that proclaims to the several social systems epistemic authority autopoietic, turning off the mechanisms of State, define what is permitted or forbidden to itself, based on its operational language, with emphasis on economic, regardless of state law. This second pre-understanding posture gives life and sets in motion the utilitarian ideology, that equivalent the preconception, directs the legislative action, and prevents any attempt to regulate the nanotechnology, and also prevents information about the risks and harms that may arise from nanotechnology. Brazilian citizens are subjected to the situation of nanotechnology guinea pig, and are kept in a condition of strategic disinformation, it gives concreteness to an inauthentic legislative stance, since rejected the constitutional principiologia as ideal good life authorized by the 1988 Constitution, particularly in relation to the duty of human formation. Advocates as a discursive stance, within the constitutional tradition and the critique of utilitarian ideology, that all progress is potentially destructive, unless it is reduced to an orderly course of nature and homeostatic relationships among citizens. And this sort only the institutionalist strand is able to provide, since it does not share the characteristics of utilitarianism insincerities. Only sincere promises are able to legitimize the future as put forward in the Magna Carta. Utilitarian insincerities can be put into perspective within the Habermasian communicative act, with the explicit understanding of rationality diverted from the constitutional rails, can be traced back to these in an argumentative pedagogy preceded by those who have already incorporated the constitutional tradition to its vital process, demonstrating through critical reflection, the reason for the incompatibility between institutionalism and utilitarianism and because the latter departs from the constitutional guidelines.
Keywords: Utilitarismo; Institucionalismo; Constituição Federal; Crítica da ideologia; Agir comunicativo; Política nacional de nanotecnologia; Utilitarianism; Institutionalism; Federal Constitution; Critique of ideology; Communicative action; National nanotechnology policy; ACCNPQ::Ciências Sociais Aplicadas::Direito